Individual and Contextual Factors Affecting DPT Immunization in Indonesia - Resti Wahyuni; Titik Harsanti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2021)
Nowadays, diphtheria cases always increase from year to year. Until now, no drug has been found to cure diphtheria, but there is the most effective way of prevention through immunization. It is known that diphtheria sufferers who don’t get immunizations increase every year. The purpose of this study is to determine the individual and contextual factors that influence the status of DPT immunization in Indonesia and its trends and to know the diversity between cities. The data used in this study are Susenas KOR and consumption and expenditure (KP) modules. The results of multilevel binary logistic regression analysis indicate that individual factors that influence the status of DPT immunization are residence classification, highest maternal education, ownership of immunization cards, birth order, and household poverty status. While the contextual are the ratio of posyandu to 100,000 population and PDRB. Characteristics of children aged 12-59 who do not get immunizations tend to live in rural areas, have mothers with the highest education in junior high school, don’t have immunization cards, who born late in households with many children, and come from poor households. Besides that, there is a diversity of characteristics between cities, which amounted to 22,19%.